2011
DOI: 10.1111/j.1349-7006.2011.01849.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer detection using infrared hyperspectral imaging

Abstract: During the last few decades, many studies have been performed on the early detection of cancer using noninvasive or minimally invasive techniques in lieu of traditional excisional biopsy. Early detection can make an immense difference because cancer treatment is often simpler and more effective when diagnosed at an early stage. Cancer detecting methods may help physicians to diagnose cancer, to dissect the malignant region with a safe margin, and to evaluate the tumor bed after resection. In this paper, the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
102
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 27 publications
1
102
0
1
Order By: Relevance
“…Using the SWIR images, the regions of ischemia were classified with a false positive rate of 8% and a false negative rate of 7%. Akbari et al 40 also performed a similar study on freshly excised human gastric tumors, using the same technology as in Ref. 39.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the SWIR images, the regions of ischemia were classified with a false positive rate of 8% and a false negative rate of 7%. Akbari et al 40 also performed a similar study on freshly excised human gastric tumors, using the same technology as in Ref. 39.…”
Section: Introductionmentioning
confidence: 99%
“…This information can potentially assist in the detection, characterization, and classification of conditions such as cancer and atherosclerosis. In fact, it has already been shown that water and lipid absorptions provide useful diagnostic "fingerprints" for detection of both cancer 8,40 and atherosclerosis. 9,14,22,23,[47][48][49] On the path toward a more widespread implementation of SWIR tissue optics measurements, one important factor to consider is the temperature dependence of tissue absorption features in the SWIR regime.…”
mentioning
confidence: 99%
“…Finally, they find that the optimized excitation wavelength of fluorescence was 420 nm. The Hamed's team used ten resected stomach to be the sample and got 101 infrared hyperspectral images [18]. They showed 90% specification.…”
Section: Introductionmentioning
confidence: 99%
“…The previous researches [1,[8][9][10][11][12][16][17][18][19] used the pushbroom structure to be the scanning mechanism of MHSI system. Figure 1(a) shows the structure of traditional pushbroom MHSI system.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperspectral imaging has also been evaluated for use in the cytologic diagnosis of cancer cells [8]. It has been reported that hyperspectral imaging is also used to detect gastric tumors in human subjects [9]. The spectral signatures of the gastric cancer and non-cancerous stomach tissue were created in infrared wavelengths.…”
Section: Introductionmentioning
confidence: 99%